El licenciado número uno, Zhang Xie, estudio preliminar y traducción de Regina Llamas, Barcelona, Bellaterra, 2014, 446. pp. - Nieves Rodríguez Valle (El Colegio de México, A.C., 2016)
El licenciado número uno, Zhang Xie, estudio preliminar y traducción de Regina Llamas, Barcelona, Bellaterra, 2014, 446. pp.